1973
DOI: 10.1111/j.1365-2818.1973.tb03784.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy at 2.5 MeV

Abstract: SUMMARY Measurements of penetration on silicon and austenitic stainless steel have been continued using the same criteria as previously reported (Thomas, 1968) up to 2.5 MeV using the 3 MeV Toulouse electron microscope. The results show that penetration increases to about 14 μm at 2.5 MeV for silicon although the curve starts to flatten out above 1.5 MeV, but no significant gain was found for stainless steel ≃2μm at 2.5 MeV). Primary knock‐on damage occurs readily in both materials. The critical voltages for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In polymers observed below 100 keV the specimen lifetime is proportional to p2 (/I = v/c) (Grubb & Groves, 1971); a similar or marginally greater proportionality, has been reported (Thomas et al, 1970) up to 1 MeV. Other workers have found much greater lifetimes even at 500 keV (Kobayashi & Ohara, 1966), and recently Thomas & Lacaze (1973) have extended measurements on the amino acids I-valine and glycine to 2.5 MeV, with dramatic increases in lifetime. If these results are substantiated the application of the HVEM to organic materials promises to be a very active field in the future !…”
Section: Reduced I O N I Z a T I O N Damagesupporting
confidence: 62%
See 1 more Smart Citation
“…In polymers observed below 100 keV the specimen lifetime is proportional to p2 (/I = v/c) (Grubb & Groves, 1971); a similar or marginally greater proportionality, has been reported (Thomas et al, 1970) up to 1 MeV. Other workers have found much greater lifetimes even at 500 keV (Kobayashi & Ohara, 1966), and recently Thomas & Lacaze (1973) have extended measurements on the amino acids I-valine and glycine to 2.5 MeV, with dramatic increases in lifetime. If these results are substantiated the application of the HVEM to organic materials promises to be a very active field in the future !…”
Section: Reduced I O N I Z a T I O N Damagesupporting
confidence: 62%
“…dislocations and stacking faults) in specimens as thick as 6-9 prn for the lightest elements such as aluminium and silicon (Humphreys et al, 1971;Thomas, 1968), 2-3 pm for medium atomic weights such as iron (Humphreys et al, 1971;Thomas, 1968;Hale, 1966), but still less than 1 pm for the heaviest elements such as gold and uranium (Humphreys et al, 1971;Foreman & Hudson, 1971). Further increases in penetration are achieved by using even higher energies, but only in the lightest elements (Thomas & Lacaze, 1973). However, as will be seen below, useful information at rather lower resolution than normally acceptable is available from much thicker specimens, particlarly of lighter materials, such as carbon fibres.…”
Section: A P P L I C a T I O N S T O T H I C K E R S P E C I M E N S mentioning
confidence: 99%
“…Recent observations up to 3 MV have confirmed trends already visible in work up to 1 MV, which showed that the relative increase in thickness is greater for light than heavy elements (see Cosslett, 1970). Thomas & Lacaze (1973) found that in silicon the thicknessvoltage curve was still rising at 2.5 MV, whereas for stainless steel there was little further increase above about 1 MV, using the visibility of stacking fault fringes as criterion. Fujita & Tabata (1973) whilst finding that the rise in aluminium was similar to that in silicon, found that for steel the curve still rose up to 3 MV.…”
Section: E T a L L U R G I C A L A P P L I C A T I O N Ssupporting
confidence: 53%
“…Dislocations in a semiconductor crystal, such as gallium nitride (GaN), degrade its optical and electrical properties. To detect and characterize lattice defects in a thick crystalline specimen which can be regarded as bulk, high-voltage electron microscopy (HVEM) is a powerful technique [1,2]. The penetration of relativistic electrons depends on imaging conditions as well as materials, and quantitative unified views regarding the maximum usable thickness have not been obtained.…”
mentioning
confidence: 99%